From screens to spontaneity: How augmented reality sparks impulse buying intention in e-commerce - Anisyah, Chumairoh Nur; Vania, Amelindha (Jurnal Mantik, 2024)
The growing prevalence of e-commerce has transformed consumer behavior, particularly in sensory-driven industries like cosmetics. However, the absence of physical interaction with products poses challenges in building consumer confidence and driving purchase decisions. Augmented Reality (AR) has emerged as a potential solution by creating vivid and interactive virtual shopping experiences. This study examined the influence of AR on impulse buying intention, with product presence as a mediating variable, focusing on Shopee’s BeautyCam feature. A quantitative approach utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze responses from 135 women aged 18–35 in East Java, Indonesia. The findings revealed that AR significantly impacted both product presence and impulse buying intention, confirming its ability to enhance consumer engagement. However, the mediating role of product presence was not statistically significant, suggesting its limited effect on impulse buying. These results highlight the direct effectiveness of AR in stimulating spontaneous purchase behavior and underline the importance of refining AR features to maximize consumer impact. This study offers insights into leveraging AR technology to address sensory gaps in e-commerce and recommends further exploration into additional factors influencing impulse buying. Future research could investigate AR applications across diverse product categories and technological advancements, broadening the understanding of AR’s role in shaping digital consumer experiences